2016
DOI: 10.1007/s10494-016-9775-9
|View full text |Cite
|
Sign up to set email alerts
|

Integral Length Scales and Time Scales of Turbulence in an Optical Spark-Ignition Engine

Abstract: In-cylinder air flow structures are known to play a major role in mixture preparation and flame development in spark-ignition engines. In this paper both LDV and PIV measurements were undertaken in an optical spark-ignition at 1500 RPM, 0.5 bar inlet plenum pressure. One of the primary PIV planes was vertical, cutting through the centrally located spark plug (tumble plane) inside the pentroof at ignition timing. The other plane was horizontal inside the pentroof 1 mm below the spark plug. LDV was conducted 1 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 67 publications
2
24
0
Order By: Relevance
“…without having injected any fuel in the intake stroke) for both vertical and horizontal planes. well as of LDV data [54,55], showed that w was slightly lower than the mean of u and v (4-5%) which effectively translated to an overestimation of the TKE by ~20% on the PIV tumble plane when using the average of u and v as an estimation for w. This should be borne in mind when making comparisons of data in the area of intersection between the two planes hereafter to avoid confusion.…”
Section: Flame Tomography Imaging and Processingmentioning
confidence: 98%
See 4 more Smart Citations
“…without having injected any fuel in the intake stroke) for both vertical and horizontal planes. well as of LDV data [54,55], showed that w was slightly lower than the mean of u and v (4-5%) which effectively translated to an overestimation of the TKE by ~20% on the PIV tumble plane when using the average of u and v as an estimation for w. This should be borne in mind when making comparisons of data in the area of intersection between the two planes hereafter to avoid confusion.…”
Section: Flame Tomography Imaging and Processingmentioning
confidence: 98%
“…To bring this into context, the integral timescale in this engine measured by LDV at ignition timing was of the order 8-16 °CA (depending on velocity component) [54,55].…”
Section: Flow Characterisationmentioning
confidence: 99%
See 3 more Smart Citations